Acceso a créditos comerciales y la gestión financiera de las mypes de la ciudad de Requena, periodo 2023 - Freyre Coral, Julio Eriberto (2023)
The objective of this thesis report was to determine the relationship between access to commercial credits and the financial management of the MSEs of the city of Requena, period 2023, in which the type study applied with the non-experimental design was used, taking as a population 180 microentrepreneurs to whom a questionnaire was applied to collect information. Therefore, access to commercial credit is rated as high, since microentrepreneurs recognize that credit history allows banks to learn from how they managed their funds before lending them a loan, and for the credit analyst to have information on all their income and expenses. For its part, financial management is rated as "high" because it has a working capital management system; the financial statement usually coincides with the International Financial Reporting Standard for MSEs. To this end, it was determined that there is a significant and positive relationship between the variables, corroborated by a coefficient and sig. of (r=0.514; p=0.000).